Extension of Anaerobic Digestion Model No. 1 and its implementation - Cesur, Durmus, author; Albertson, Maurice L., advisor; Henk, Linda L., committee member; Pruden-Bagchi, Amy J., committee member; Julien, Pierre Y., committee member; Siddiqui, Mohammed M., committee member (Colorado State University. Libraries, 2004)
The Anaerobic Digestion Model No. 1 (ADM1) from the IWA Task Group is modified to accommodate accumulation of swine manure in the digester. The Modified Model offers a physically-based methodology to solve for an unsteady state (i.e., variation in hydraulic retention time, HRT). The methodology is used to estimate the decrease in operating volume and the increase in retention time due to biomass recycling in the reactor caused by the accumulation of particulate matter and operational variations. The methodology is unique in that it considers both the reduction in the operating volume and the increase in retention time simultaneously. The methodology developed and incorporated into the Original Model is one of the first attempts to generalize the anaerobic digestion (AD) process modeling to account for unsteady state operation which is generally the observed case for full-scale reactors. Generalization for unsteady state is especially important for the reactor start-up period, which is a very critical time frame that determines the future operation of the reactor. The Modified Model has been verified and used for the optimization of the anaerobic digestion in a Colorado Pork (CP) waste reactor. The Modified Model simulation has a 10 % relative error, which is a lower error than the 15.6 % relative error of the Original Model simulation. The Modified Model outputs are evaluated and compared with the original model outputs. The conclusions that are drawn are as follows: a. The physically-based modification methodology, developed in the research, is suitable and necessary for simulation of the anaerobic digestion in a Colorado Pork anaerobic digester. b. The Modified Model is suitable for use in optimization studies. The Modified Model can be used to test the outputs of various digester management practices. The comparison of the Modified Model results with the Original Model results has clearly shown that the modification is necessary to simulate the effects of accumulation on the AD process.
Keywords: civil engineering; agricultural engineering